﻿Building Upon Success: A multi-perspective study of Speech, Language and Communication Needs in adolescence - Degabriele, James (School of Linguistic, Speech and Communication Sciences . Discipline of Clinical Speech & Language Studies, 2018)
Background Adolescence is a life stage characterised by important and significant growth in the areas of physical, cognitive, social and language development, which have a strong influence on individual outcomes in adulthood. It is estimated that around 10% of adolescents have speech, language and communication needs (SLCN). Having SLCN in adolescence can have a pervasive negative impact on academic achievement, mental health, and social interaction, among others. However, certain protective factors, such as good support and prosocial attitudes can mitigate the negative impact of SLCN. Furthermore, intervention studies show that speech and language therapy (SLT) interventions can be effective with this age group. Given the potential impact of SLCN in adolescence, speech and language therapists (SLTs) and other professionals have a duty to try to prevent such negative repercussions. Increased knowledge and awareness about protective factors and effective interventions should be integrated to more fully inform our understanding of adolescents with SLCN. Gaining a more holistic view of adolescents with SLCN requires consultation with the adolescent him/herself and associated networks of family, school and SLT services. Aims The aims of this research were (i) to identify the social, communicative and learning experiences of adolescents with SLCN, as perceived by those closest to them and by the adolescents themselves and (ii) to find out how speech and language therapists can best meet the needs of adolescents with SLCN holistically, with these social, communicative and learning experiences in mind. Methods Participants, including SLTs, adolescents, parents and educators, were recruited to explore their experiences as related to SLCN. A number of methods were used to collect data from these key stakeholders, as follows: 1. online survey of SLTs (n=50) iv 2. online survey of a generic sample of adolescents (n=91) (adolescents with SLCN were not excluded) 3. semi-structured interviews with parents of adolescents with SLCN (8 participants) 4. focus groups with educators in mainstream secondary schools (three focus groups) 5. focus group with adolescents with SLCN (5 participants) using visual/participatory methods A variety of both quantitative and qualitative methodologies were used to analyse the data, as follows: descriptive statistics (1,2), Interpretative Phenomenological Analysis (IPA) (3) and Thematic Analysis (4,5). Results A rich and diverse set of results was obtained. These results help inform how adolescents and their networks experience SLCN and consequent impact, which in turn can inform tailored and realistic SLT services and supports for all stakeholders. Key results were identified in six areas (a) the impact of SLCN on people's lives, (b) social functioning, (c) services and supports, (d) educational achievement, (e) psychological wellbeing and (f) thinking about the future/preparation for life. Taking due account of - yet moving beyond - the negative impact of SLCN was key to the experience of all concerned. Discussion and Conclusions Results suggest that a philosophical shift is needed from a narrow, impairment-focused view to a multi-dimensional understanding of adolescents with SLCN. The multi-dimensional view should take into account the broad impact of SLCN on the lives of adolescents and the lives of those around them. Secondly, results indicate that the best outcomes for adolescents with SLCN are obtained when there is a focus on experiencing success. It is proposed that the principle of Building Upon Success (BUS) should be adopted by service providers to enable adolescents with SLCN to experience repeated success (despite their SLCN) in the activities they participate in. The experience of success builds confidence and promotes psychological wellbeing. The implications of adopting the BUS principle in practice are discussed with respect to the person, the process(es) and the organisations involved.
Keywords: speech, language and communication needs (SLCN)